2019
DOI: 10.1519/jpt.0000000000000135
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Falls in Older Adults With Mild Cognitive Impairment and Mild Alzheimer Disease

Abstract: Careful attention should be given to dual-task and turn-to-sit activities when detecting risk of falls among older people with MCI and mild AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(86 citation statements)
references
References 29 publications
3
82
0
1
Order By: Relevance
“…Previous studies also report a greater number of older women with MCI. 22,23 Moreover, the AD group had a lower calorie expenditure compared to the PC group, which is in line with data described by Pedroso et al, 24 who also found that older people with AD have low activity levels. Regarding the number of medications and diseases, higher numbers were found in individuals with cognitive impairment.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Previous studies also report a greater number of older women with MCI. 22,23 Moreover, the AD group had a lower calorie expenditure compared to the PC group, which is in line with data described by Pedroso et al, 24 who also found that older people with AD have low activity levels. Regarding the number of medications and diseases, higher numbers were found in individuals with cognitive impairment.…”
Section: Discussionsupporting
confidence: 87%
“…In a longitudinal study with a six-month follow-up using a fall calendar and monthly phone calls, 52.6% of the individuals with MCI and 51.4% of those with mild AD experienced falls. 22 The level of physical activity, participation in social activities and the supervision of caregivers can influence the exposure of older people to a variety of environmental stimuli that can exert an impact on the risk of falls. Moreover, the 32-month period increases the risk of recall bias and the prevalence of falls may actually be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] There is an increasing understanding that motor impairments contribute to overall AD severity, and that there is a need for ameliorating these impairments. For example, gait impairments can decrease quality of life by reducing mobility; increasing risk for injuries due to falling and increasing the likelihood of institutionalization once the ability to walk is lost 10,11 . Motor dysfunction is a reliable predictor for the development of AD, and can also predict levels of cognitive dysfunction and mortality risk.…”
Section: Introductionmentioning
confidence: 99%
“…MCi has been classified as one of the fall risk factors in older people [7]. According to estimates, more than half of the older population regularly experience falls [8,9]. However, the cause of the increased fall risk in this population is not entirely clear [10].…”
Section: Introductionmentioning
confidence: 99%